2018
DOI: 10.1111/ahe.12335
|View full text |Cite
|
Sign up to set email alerts
|

Comparative histomorphological study of endometrium in mares

Abstract: Uterine acute post-breeding inflammation is a physiological tissue response to the entry of exogenous elements, with persistent endometritis being the main pathology responsible for subfertility in the mare (Equus ferus caballus; Linnaeus, 1758). Mares can be classified as susceptible or resistant to endometritis according to their ability to remove intrauterine fluid within 48 hr after experimental inoculation. Endometrial biopsy is a technique that is commonly used to establish the degree of lesions that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The body condition score of mares at foaling and balanced nutritional support provided by permanent grazing warrants adequate nutritional reserve to support lactation, resumption of ovarian cyclicity, and fertile postpartum ovulation while lactating the foals [ 54 , 55 , 56 ]. Finally, differences in peripartum follicular dynamics between PM and NPM groups could be due to individual variations, as if the NPM group were more susceptible than the NP group to postpartum uterine inflammation as reported for cycling mares [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The body condition score of mares at foaling and balanced nutritional support provided by permanent grazing warrants adequate nutritional reserve to support lactation, resumption of ovarian cyclicity, and fertile postpartum ovulation while lactating the foals [ 54 , 55 , 56 ]. Finally, differences in peripartum follicular dynamics between PM and NPM groups could be due to individual variations, as if the NPM group were more susceptible than the NP group to postpartum uterine inflammation as reported for cycling mares [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have been carried out on END there is no complete understanding of the etiopathogenesis of this disease (England et al 2021). A study reported that epithelial heigh, glandular diameter, and density were greater in susceptible mares than in resistant to persistent post-breeding END during estrus (Herrera et al 2018). In contrast, in the current study, ET, GC height, and glandular density did not change between NE and END.…”
Section: Discussionmentioning
confidence: 99%
“…1B-1D). A study reported that epithelial heigh, glandular diameter, and density were greater in susceptible mares than in resistant to persistent post-breeding END during estrus (Herrera et al 2018). In contrast, ET, GC height, and glandular density did not change between NE and END in this study.…”
Section: Discussionmentioning
confidence: 99%